2021
DOI: 10.3390/pr9091673
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Analysis of the Effect of Impeller Rounding on Centrifugal Pump as Turbine

Abstract: Pump as turbine (PAT) is one of the micro-hydro system components. It can be used alone as a generator in remote areas without power supply, and in hydraulic networks instead of pressure-reducing valves. However, its hydraulic optimization still remains an open research problem. One of the optimization techniques is the rounding of the sharp edges at the blade periphery. Existing studies are mostly based on prototype experiments to obtain the optimization effect. In order to more intuitively analyze the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The increase the number of Z1 resulted in a slight decrease in the slopes of the H-Q curve, causing t curve to flatten, which was in line with the theoretical analysis. This was also the result Equation (17). However, as Z1 changed, the slope of the curve decreased continuous leading to a decrease in PAT efficiency and a narrowing of the high-efficiency zone.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The increase the number of Z1 resulted in a slight decrease in the slopes of the H-Q curve, causing t curve to flatten, which was in line with the theoretical analysis. This was also the result Equation (17). However, as Z1 changed, the slope of the curve decreased continuous leading to a decrease in PAT efficiency and a narrowing of the high-efficiency zone.…”
Section: Resultssupporting
confidence: 68%
“…The slopes of the H-Q curve decreased significantly with the increase in A3, which was consistent with the theoretic analysis, but the decreasing amplitude also gradually slowed down. In the derived Equ tion (17), the second-order mixed partial derivative was used to derive the change in slop and the conclusion was that in order to flatten the H-Q curve, α3 had to be increased. A ditionally, as A3 increased, the maximum PAT efficiency gradually increased at a slowi rate, and the efficiency point shifted towards a higher flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…With the development of computer technology and fluid theory, a numerical simulation based on computational fluid dynamics (CFD) has been widely used in fluid machinery research. Yang et al, (2021) used CFD to study the effect of blade fillets on PAT performance and found that the efficiency was improved by 8.09% at 1,500 rpm. Adu et al (2021) studied the effect of splitter blades on the performance of PATs under different rotational speeds and flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have proposed low-cost, simple modifications for the impeller and volute (geometrical modifications) to increase the performance of PAT, keeping cost benefits intact. One such simple modification involves rounding of the impeller blades and shrouds [5][6][7][8][9], which altogether may contribute 1 to 1.5 % enhancements in the PAT performance. Some researchers proposed a method of back cavity filling with solid material of appropriate size and shape to reduce the disk friction loss and to increase the PAT efficiency [10].…”
Section: Introductionmentioning
confidence: 99%